Perbandingan Parameter Return-Loss, VSWR dan Gain Terhadap Elemen Driven Antena Yagi 450 MHz - Darwis, Rizadi Sasmita; Azwar, Hamid; Diono, Muhammad (Jurnal ELEMENTER (Elektro dan Mesin Terapan), 2023)
Inequality in infrastructure development, especially in rural or rural areas, is the main obstacle for people to access the internet. An antenna capable of operating at the LTE 450 MHz frequency is needed so that the LTE network reaches rural areas and people who live in rural areas are easy to access quality internet services. The radiation pattern possessed by the Yagi antenna is useful for making the Yagi antenna the right solution to solve this problem. In this research, the design and performance comparison of Yagi antennas with different driven elements is carried the gas trhotle on the bicycle handlebar, the brushless motor at the bottom near the bicycle pedal out, namely driven batang aluminium Yagi antennas and driven planar Yagi antennas. The driven batang aluminium Yagi antenna and driven planar Yagi antenna are designed to have 10 elements consisting of 1 reflector element, 1 driven element and 8 director elements and can operate properly at a frequency of 450 MHz. The parameters obtained from the measurement results of the Yagi rod alumminium driven and the planar driven meet the desired specifications. The return-loss values of the aluminium rod driven Yagi antenna and planar driven Yagi antenna at a frequency of 450 MHz are -25.68 dB and -20.09 dB. The bandwidth of the two antennas has met the uplink frequency (452.5 MHz – 457.5 MHz) and downlink frequency (462.5 MHz – 467.5 MHz). The VSWR values of the rod aluminium driven Yagi antenna and the planar driven Yagi antenna are 1.11 and 1.22 with gains of 13.31 dBi and 8.18 dBi, respectively. The radiation pattern of a Yagi antenna with a rode aluminium dan planar driven is directional.